The effect of Ramadan fasting on sebum production: association with nutritional intakes and sleeping pattern - Rosmelia, -; Setyopranoto, Ismail; Hadi, Hamam; Wirohadidjojo, Yohanes Widodo (Bangladesh Journal of Medical Science, 2019)
Background: Sebum production is associated with several factors including hormonal, and nutritional factors. Sleeping pattern could also affect changes in androgen levels associated with sebum production and acne. During Ramadan, moslems are obliged to fast from dawn to sunset, causing nutritional intake and sleeping pattern changes. Objectives: This study was aimed to find association between nutritional intake and sleeping pattern during Ramadan with sebum production. Methods: Ramadan fasting practitioners (40 male, mean age ±SD : 19.19±1.03 years) were evaluted before and 3 weeks into Ramadan fasting. Parameters assessed were nutrient intakes (using 24-hour food recalls), sleep quality and duration (using Pittsburgh Sleep Quality Index) and sleep diary. Sebum productions were measured using SebutapeR technique. Results: Significant decreases were found in protein (p=0.014), total fat (p=0.031), milkshake(p=0.001) and cheese intakes (p=0.013). Glycemic load was also decreased significantly (p=0.006). Despite no reduction in total sleep duration, night sleep duration was significantly reduced during Ramadan (p=0.000) associated with more subjects with poor sleep quality (p=0.039). Sebum production was increased significantly during Ramadan (p=0.028) Conclusion: Despite lower glycemic load and dairy products intakes, and lower sleep duration, Ramadan fasting was associated with increased sebum production. It was likely a result of circadian rhythm shift in sebaceous glands activities. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.546-551